Pengaruh Profitabilitas, Leverage, Kompensasi Bonus, dan Kepemilikan Institusional terhadap Praktik Perataan Laba - Univera, Ribeta Lyrae; Yusuf , Muhammad; Ulupui, I Gusti Ketut Agung (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This research aims to determine the effect of profitability, leverage, bonus compensation, and institutional ownership. The independent variables used in this research are profitability, leverage, bonus compensation, and institutional ownership. The dependent variable used is income smoothing. This research uses secondary data, namely financial reports and annual reports of non-financial companies listed on the Indonesia Stock Exchange for the 2017-2022 period (318 observations). The sampling method used in this research was purposive sampling method. The method used in this research is logistic regression analysis which is processed using the SPSS version 25 application. The research results show that profitability has no effect on income smoothing, leverage has no effect on income smoothing, bonus compensation has a negative effect on income smoothing, and institutional ownership has a negative effect on income smoothing.